Pengaruh Corporate Governance Terhadap Restatement dan Dampaknya Terhadap Harga Saham - Nolita Yeni Siregar; Fitria Rahayu (Politeknik Negeri Lampung, 2018)
This study aims to prove empirically the influence of corporate governance proxied by the size of the board of commissioners, the independence of the board of commissioners, the size of the audit committee, managerial share ownership and institutional share ownership as well as its impact on stock prices. The data used in this research is secondary data. The population in this study is a public listed company listed on the Indonesia Stock Exchange period 2013-2015. The analysis technique used is logistic regression analysis. The test results prove that the size of the board of commissioners, the size of the audit committee and managerial share ownership, negatively negatively affect the restatement, while the independence of the board of commissioners and institutional ownership have no significant significant effect on the restatement and restatement negatively effect on stock prices.Â Keywords: Board size, board independence, audit committee , managerial share ownership, institutional share ownership, restatement, stock priceÂ